Mixed Ligand Complexes of N-Methyl-N-phenyl Dithiocarbamate: Synthesis, Characterisation, Antifungal Activity, and Solvent Extraction Studies of the Ligand - Anthony C. Ekennia; Damian C. Onwudiwe; Cyril Ume; Eno E. Ebenso (Bioinorganic Chemistry and Applications)
A series of mixed ligand dithiocarbamate complexes with a general formula [ML2(py)2], where M = Mn(II), Co(II), Ni(II), and Cu(II), py = pyridine, and L = N-methyl-N-phenyl dithiocarbamate have been prepared and characterised by elemental analysis, FTIR and Uv spectroscopy, magnetic moment, and thermogravimetric and conductance analysis. The infrared spectra showed that symmetrical bidentate coordination occurred with the dithiocarbamate moiety through the sulfur atoms, while neutral monodentate coordination occurred through the nitrogen atom for the pyridine molecule in the complexes. The electronic spectra, elemental analysis, and magnetic moment results proved that the complexes adopted octahedral geometry. The conductance measurement showed that the complexes are nonelectrolytes proving their nonionic nature. The compounds were screened for three human pathogenic fungi: Aspergillus flavus, Aspergillus niger, and Candida albicans. The cobalt complex showed the best antifungal activity among the test compounds. Liquid-liquid extractive abilities of the ligand towards copper and nickel ions in different solvent media were investigated. The ligand showed a strong binding affinity towards the metals ions with an extractive efficiency of about 99%.